Hesi after 50 years and 130 years: beginning a new generation of Hesi research - Spencer, John R.; Hardin, James W.; Blakely, Jeffrey A. (Joint Archaeological Expedition to Tell el-Hesi, 2024)
Tell el-Hesi is located near the modern city of Qiryat Gat in the Southern District of Israel, 23 kilometers from the Mediterranean Sea. The site, which covers 35–40 acres, includes both an acropolis and a lower city. Occupation of the site began as early as the Neolithic period, and the city grew significantly during the Early Bronze Age before being abandoned until the Late Bronze Age. The latest phase of occupation occurred during the Hellenistic period. The acropolis was in use for almost two thousand years. This volume is the first in a new iteration of the Joint Archaeological Expedition to Tell el-Hesi series that builds on previously published volumes. It publishes a final report for part of one of Tell el-Hesi’s excavation fields; a reevaluation of the stratigraphic findings of the original 1891–1892 excavations on Tell el-Hesi, based on excavation work from the 1970s and 1980s; in-depth studies of groups of small finds from the tell; and zooarchaeological analyses that widen the investigative perspective to include the region around the tell.Paying tribute to the long excavation history at Tell el-Hesi, the contributors to this volume employ state-of-the-art scientific methods that honor the careful work and findings of a century of excavations. Hesi After 50 Years and 130 Years will be an important reference for scholars researching the history and culture of southern Palestine